Practical feasibility, scalability and effectiveness of coordinated scheduling algorithms in cellular networks towards 5G. (15th March 2018) - Nardini, G.; Stea, G.; Virdis, A.; Frangioni, A.; Galli, L.; Sabella, D.; Dell'Aera, G.M.
Abstract: Coordinated Scheduling (CS) is used to mitigate inter-cell interference in present (4G) and future (5G) cellular networks. We show that coordination of a cluster of nodes can be formulated as an optimization problem, i.e., placing the Resource Blocks (RB) in each node's subframe with the least possible overlapping with neighboring nodes. We provide a clever formulation, which allows optimal solutions to be computed in clusters of ten nodes, and algorithms that compute good suboptimal solutions for clusters of tens of nodes, fast enough for a network to respond to traffic changes in real time. This allows us to assess the relationship between the scale at which CS is performed and its benefits in terms of network energy efficiency and cell-edge user rate. Our results, obtained using realistic power, radiation and Signal-to-Interference-and-Noise-Ratio (SINR) models, show that optimal CS allows a significant protection of cell-edge users. Moreover, this goes hand-in-hand with a reduction in the number of allocated RBs, which in turn allows an operator to reduce its energy consumption. Both benefits actually increase with the size of the clusters. The evaluation is carried out in both a 4G and a foreseen 5G setting, using different power models, system bandwidths and SINR-to-datarate mappings.